GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Direct ultrastructural validation of endocrine cell identity in zebrafish pancreatic islets - N. Schmitner; C. Deseife; A. Neumann; W. Salvenmoser; A. C. Seybold; R. A. Kimmel; D. Meyer (Cell and Tissue Research, 2026)
The zebrafish is widely used to study glucose homeostasis, diabetes, and endocrine cell plasticity, yet a definitive ultrastructural characterization of adult pancreatic endocrine cell types has remained incomplete. Here, we combined transmission electron microscopy with hormone-specific immunogold labeling to define the ultrastructural characteristics of the major endocrine cell populations in adult zebrafish pancreatic islets. Three principal endocrine cell types were distinguished based on secretory granule morphology, electron density, and intracellular organization. Glucagon-positive α-cells contained electron-dense granules with a characteristic halo and eccentric dense core, insulin-positive β-cells displayed larger moderately electron-dense granules, and somatostatin-positive δ-cells possessed smaller, predominantly electron-dense granules of heterogeneous shape. Immunogold labeling for glucagon, insulin, and somatostatin linked granule ultrastructure to endocrine cell identity. To independently validate β-cell assignment, we performed nitroreductase-mediated β-cell ablation in juvenile zebrafish and observed a marked depletion of cells containing the characteristic medium electron-dense granules. Comparative analysis indicates that zebrafish endocrine granule ultrastructure differs in several respects from mammalian islets and exhibits similarities to selected teleost species, highlighting evolutionary diversity in endocrine granule organization. This study provides a foundational ultrastructural reference for the three major endocrine cell types of the adult zebrafish endocrine pancreas and establishes criteria for identifying these populations in studies of pancreatic disease, regeneration, and cell plasticity while also identifying an additional unassigned endocrine population that warrants further characterization.

Identification of the cereal leafminer (Syringopais temperatella) tolerance sources in a spring barley core collection and their genome-wide genetic dissection - Adel H. Abdel-Ghani; Rasha A. Tarawneh; Saddam A. Al-Dalain; Yacoub Emeel Hijazeen; Mahmud A. Duwayri; Soud Abbadi; Yehya Alattal; Saed J. Owais; Sobhia Saifan; Huda Hazim Al-Taae; Benjamin Kilian; Kerstin Neumann (Genetic Resources and Crop Evolution, 2026)

Mycorrhizal identity and light shape tree seedling biomass responses in plant–soil feedbacks - Sarah McCarthy-Neumann; Katherine E. A. Wood; Richard K. Kobe (Plant and Soil, 2026)
Aims Plant–soil feedbacks (PSFs) are key drivers of forest composition and diversity, yet their direction and magnitude may depend on the mycorrhizal identity of interacting species, environmental conditions, and experimental context. Methods We conducted complementary greenhouse and field experiments using Acer rubrum L., Acer saccharum Marsh., Prunus serotina Ehrh. (all arbuscular mycorrhizal [AM] species), and Quercus alba L., and Quercus rubra L. (all ectomycorrhizal [EM] species) to test how biomass-based PSFs vary with mycorrhizal matching between seedlings and adult trees, light availability, and soil microbial communities. Seedlings were grown in soil conditioned by conspecifics, conmycorrhizal heterospecifics, or heteromycorrhizal heterospecifics under controlled and natural light regimes. Results Consistent with expectations, AM species consistently exhibited negative PSFs under low light, and EM species tended to show more positive PSFs, but this pattern was contingent on light and greenhouse versus field setting. For AM species, negative PSFs occurred primarily under low light and were neutralized or reversed under higher light. EM species showed generally more positive PSFs across light levels and settings, although species-specific differences emerged. PSFs were driven largely by conspecific soil conditioning, with limited influence from the mycorrhizal identity of heterospecific neighbors. Results from greenhouse versus field settings diverged, with field PSFs sometimes attenuated or reversed, particularly for Q. alba. Conclusions These findings highlight that biomass-based PSFs are not fixed species traits but context-dependent outcomes influenced by mycorrhizal type, light availability, and environmental setting. Incorporating these factors is essential for predicting how PSFs influence seedling recruitment, forest dynamics, and biodiversity.

Mirtazapine is a functional antagonist at cardiac human H1-histamine receptors - Thanh Hoai Pham; Jonas M. A. Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Mirtazapine is an atypical tetracyclic antidepressant drug that binds to several monoamine neurotransmitter receptors. For instance, mirtazapine binds to H 1 -histamine receptors in vitro and in the brain of patients in vivo. Here, we hypothesize that mirtazapine is an antagonist at human cardiac H 1 -histamine receptors. To test this hypothesis, we measured force of contraction in isolated electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult transgenic mice with cardiomyocyte-specific overexpression of the human H 1 -histamine receptor (H 1 -TG). These findings were compared with those in wild-type littermate mice (WT). Finally, we measured the force of contraction in isolated electrically stimulated right atrial muscle strips (HAP) gotten from adult patients who were undergoing bypass surgery. Mirtazapine concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in LA and RA from H 1 -TG. Importantly, mirtazapine (starting at 100 nM) concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in HAP. We thus conclude that mirtazapine can antagonize human cardiac H 1 -histamine receptors at therapeutic drug concentrations, and thus, mirtazapine may have cardiac untoward effects in psychiatric patients.

Association between cardiovascular-kidney-metabolic syndrome and risks of 14 age-related health outcomes in primary prevention older population - Zhen Zhou; Kevan R. Polkinghorne; Andrew M. Tonkin; Robyn L. Woods; Anping Cai; Sophia Zoungas; Michelle A. Fravel; Michael E. Ernst; Chao Zhu; Mark Nelson; Johannes T. Neumann; Kerry M. Sheets; et al. (GeroScience, 2026)

Challenges in measuring the size and velocity of large raindrops: a comparison of selected methods - M. Beczek; M. Neumann; R. Mazur; D. Zumr; T. Dostal; A. Bieganowski (Journal of Hydrology, 2025)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Vegetation and climate dynamics in a 16,600-year marine sequence offshore Mozambique in Delagoa Bight, south-eastern Africa - F.H. Neumann; J. Finch; A. Hahn; C.S. Miller; L. Scott; E. Schefuß; L. Dupont; H.C. Cawthra; F. Engelbrecht (Quaternary International, 2025)

Cretaceous–Paleogene palynodebris from two offshore cores in Cape Basin, South Atlantic Ocean and their paleoenvironmental implications - A. Sandersen; L. Scott; F.H. Neumann; E.W. Bergh; M. Bachari (Palaeoworld, 2025)

P24-23 Key Agronomic and Safety Characteristics (Key ASCs) and why they matter to improve safety and reduce reliance on animal testing for agricultural solutions - M. Corvaro; M. Battalora; L. Bertomeu; S. Ellis; I. Fegert; J.-C. Garcin; S. Kan-King-Yu; T. Mehta; S. Nadzialek; B. Neumann; P. Rawlinson; U. Rooni; et al. (Toxicology Letters, 2025)

Simulating Carbon Mineralization at Pore Scale in Capillary Networks of Digital Rock - David A. Lazo Vasquez; Jaione Tirapu Azpiroz; Rodrigo Neumann Barros Ferreira; Ronaldo Giro; Manuela Fernandes Blanco Rodriguez; Matheus Esteves Ferreira; Mathias B. Steiner (Transport in Porous Media, 2025)
Predicting the geometrical evolution of the pore space in geological formations due to fluid–solid interactions has applications in reservoir engineering, oil recovery, and geological storage of carbon dioxide. However, modeling frameworks that combine fluid flow with physical and chemical processes at a rock’s pore scale are scarce. Here, we report a method for modeling a rock’s pore space as a network of connected capillaries and to simulate the capillary diameter modifications caused by reactive flow processes. Specifically, we model mineral erosion, deposition, dissolution, and precipitation processes by solving the transport equations iteratively, computing diameter changes within each capillary of the network simultaneously. Our automated modeling framework enables simulations with digital rock samples as large as (1.125 mm) $$^3$$ 3 having 125 $$×$$ × 10 $$^6$$ 6 voxels, within seconds of CPU time per iteration. As an application of the computational method, we have simulated brine injection and calcium carbonate precipitation in sandstone. For quantitatively comparing simulation results obtained with models predicting either a constant or a flow rate-dependent precipitation, we track the time-dependent capillary diameter distribution as well as the permeability of the connected pore space. For validation and reuse, we have made the automated simulation workflow, the reactive flow model library, and the digital rock samples available in public repositories.

Applying the science impact framework to understand real-world applications and impacts of ICESat and ICESat-2 data on decision-making - Siobhan L. Light; Molly E. Brown; Aimee R. Neeley; Thomas A. Neumann (Remote Sensing Applications: Society and Environment, 2025)

Clozapine is a functional antagonist at cardiac human H2-histamine receptors - Jonas M. A. Schlicht; Undine Ahlrep; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Clozapine is an atypical antipsychotic (neuroleptic) drug. Clozapine binds to H 2 -histamine receptors in vitro. We wanted to test the hypothesis that clozapine might be a functional antagonist at human cardiac H 2 -histamine receptors. To that end, we studied isolated electrically stimulated left atrial preparations and spontaneously beating right atrial preparations from transgenic mice with cardiomyocyte-specific overexpression of the human H 2 -histamine receptor (H 2 -TG). For comparison, we used wild-type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium (HAP) obtained from patients during bypass surgery. After pre-stimulation with histamine, clozapine (up to 10 µM) concentration and time dependently decreased beating rate in right atrial preparations from H 2 -TG. Clozapine concentration dependently 1, 3, and 10 µM decreased histamine-stimulated force of contraction in HAP. Clozapine (10 µM) decreased also the isoprenaline-stimulated force of contraction in HAP. In summary, clozapine can antagonize the function of H 2 -histamine and β-receptors in the human heart.

Genome-wide association study of Fuchs’ endothelial corneal dystrophy in the German population - Juliane Fechner; Guilherme B. Neumann; Fabia Murza; Leonard Matthias; Marcus Walckling; Claudia Brockmann; Thomas A. Fuchsluger; Tobias Brockmann (Human Genetics, 2025)
The genetic etiology of Fuchs Endothelial Corneal Dystrophy (FECD) is not yet fully elucidated. While the disease is widespread and the leading indication for corneal transplantation in the Western world, the concurrent shortage of corneal transplants underscores the urgent need for further research into the underlying mechanisms. Such investigations could enable the development of innovative therapeutic strategies. Therefore, we aimed to verify candidate genes previously identified and sought after novel variants in the German population. Undertaking a genome wide association study (GWAS) using the Axiom™ Precision Medicine Diversity Array on 157 FECD cases and 309 controls, followed by pathway enrichment analysis, we were able to confirm the significance of the TCF4 locus (rs613872, p = 8.0 × 10 − 23 , OR = 8.60, h 2 = 0.72) and identified a range of novel variants. Further fine-mapping highlighted novel candidate SNPs, such as on chromosome 5 in the SEMA6A gene (rs153643, p = 3.1 × 10 − 9 , OR = 2.75, h 2 = 0.30), and on chromosome 19 in the DNAJC19P3 gene (rs62117964, p = 3.3 × 10 − 8 , OR = 3.61, h 2 = 0.29). SEMA6A gene is involved in apoptotic pathways and cytoskeletal remodeling, making it an interesting candidate gene for further investigations as a potential therapeutic target. Furthermore, several variants were identified in lncRNAs, which presumably influence the expression of nearby protein-coding genes. For example, LOC105372130 , which is associated with corneal hysteresis and corneal resistance factor, may influence the expression of TCF4 .

Arsenic and zinc cycling in Cambodian rice fields of the Tonle Sap floodplain - Yasmine A. Farhat; E-Nieng Muth; Chou Cheythyrith; Lyda Hok; Gordon W. Holtgrieve; Soo-Hyung Kim; Rebecca B. Neumann (Science of The Total Environment, 2025)

Litter and fire risks in nonequilibrium ecosystems: Issues for Australian institutions and a response to Sharples et al. - Mark A. Adams; Mathias Neumann (Forest Ecology and Management, 2025)

Phylogenetic characterization of Bifidobacterium kimbladii sp. nov., a novel species from the honey stomach of the honeybee Apis mellifera - M. Modesto; D. Scarafile; A. Vásquez; R. Pukall; M. Neumann-Schaal; S. Pascarelli; B. Sgorbati; M. Ancora; C. Cammà; P. Mattarelli; T.C. Olofsson (Systematic and Applied Microbiology, 2025)

Landscape structure affects temporal dynamics in the bumble bee virome: Landscape heterogeneity supports colony resilience - Laura Bosco; Orlando Yañez; Alexandria Schauer; Corina Maurer; Samuel A. Cushman; Raphaël Arlettaz; Alain Jacot; Torsten Seuberlich; Peter Neumann; Daniel Schläppi (Science of The Total Environment, 2024)

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

The thermal structure of the Colombian lithosphere: A regional and basin-scale analysis - Harold Buitrago; Florian Neumann; Juan Contreras; Carlos A. Vargas (Tectonophysics, 2024)

SIMULATeQCD: A simple multi-GPU lattice code for QCD calculations - Lukas Mazur; Dennis Bollweg; David A. Clarke; Luis Altenkort; Olaf Kaczmarek; Rasmus Larsen; Hai-Tao Shu; Jishnu Goswami; Philipp Scior; Hauke Sandmeyer; Marius Neumann; Henrik Dick; et al. (Computer Physics Communications, 2024)

Correction: Afromontane forests and human impact after the African Humid Period: wood charcoal from the Sodicho rock shelter, SW Ethiopian highlands - Stéphanie C. Bodin; Katharina Neumann; Elena A. Hensel; Ralf Vogelsang; Sebsebe Demissew; Manuel Casas-Gallego; Karen Hahn (Vegetation History and Archaeobotany, 2024)

Afromontane forests and human impact after the African Humid Period: wood charcoal from the Sodicho rock shelter, SW Ethiopian highlands - Stéphanie C. Bodin; Katharina Neumann; Elena A. Hensel; Ralf Vogelsang; Sebsebe Demissew; Manuel Casas-Gallego; Karen Hahn (Vegetation History and Archaeobotany, 2024)
The SW highlands of Ethiopia are a key component in the evolution of modern humans. Yet, palaeoecological studies, essential to understand past human-vegetation relationships, are almost inexistent in this region. In this paper, we present an anthracological study of the Sodicho rock shelter, located at 1,930 m a.s.l. in the SW Ethiopian Afromontane forest zone, reconstructing the past woody vegetation since the end of the African Humid Period (ca. 5,000 cal bp ). Our results show that the vegetation around the rock shelter from ca. 4,750 to 1,750 cal bp was an ecotone between Afromontane forest and wooded grasslands of the lowlands, maintained open by the use of fire, although the climatic conditions were favourable for closed forest. The charcoal assemblage also demonstrates strong wood selection, with Syzygium guineense , Acacia and Proteaceae as the preferred taxa, even during a volcanic event when human occupation had been assumed to be absent. We therefore suggest that the rock shelter might have been visited more continuously than previously thought. Finally, under less intense occupation activities from ca. 1,700 to 300 cal bp , forest taxa became comparatively more dominant than before, as documented in the charcoal record. This demonstrates that the forest can recover under reduced human impact. The fact that the Afromontane forest is resilient is of utmost importance, indicating that reforestation is still possible despite the strong agricultural and demographic pressures the Ethiopian highlands are currently facing.

Perspective: Flawed assumptions behind analysis of litter decomposition, steady state and fire risks in Australia - Mark A. Adams; Mathias Neumann (Forest Ecology and Management, 2024)

Women and Authorship in Medical Toxicology: Canaries in the Coal Mine - Natalie R. Neumann; Gillian A. Beauchamp (Journal of Medical Toxicology, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

Proline and Silver Nitrate Promotes Multiple Shoot Induction from Mature Embryo and Shoot Tip Explants of Sorghum - B. D. Pawar; N. R. Markad; R. S. Wagh; M. Neumann; A. A. Kale; V. P. Chimote (Sugar Tech, 2023)

When does temperature matter? Response of rice arsenic to heat exposure during different developmental stages - Yasmine A. Farhat; Soo-Hyung Kim; Rebecca B. Neumann (Plant and Soil, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Carbapenemase-producing Gram-negative bacteria in hospital wastewater, wastewater treatment plants and surface waters in a metropolitan area in Germany, 2020 - Markus Hoffmann; Martin A. Fischer; Bernd Neumann; Katja Kiesewetter; Ines Hoffmann; Guido Werner; Yvonne Pfeifer; Christoph Lübbert (Science of The Total Environment, 2023)

Correction: Amycolatopsis camponoti sp. nov., new tetracenomycin‑producing actinomycete isolated from carpenter ant Camponotus vagus - Yuliya V. Zakalyukina; Ilya A. Osterman; Jacqueline Wolf; Meina Neumann‑Schaal; Imen Nouioui; Mikhail V. Biryukov (Antonie van Leeuwenhoek, 2023)

Carbohydrates in Kangaroo grass (Themeda triandra Forssk.) grain and perspectives on its food potential - James M. Cowley; Aaron L. Phillips; Shi Fang Khor; Tycho Neumann; Wai Li Lim; Rachel A. Burton (Journal of Cereal Science, 2023)

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

There is a trade-off between forest productivity and animal biodiversity in Europe - C. N. Khamila; T. A. Groen; A. G. Toxopeus; L. Santini; M. Neumann; C. Van Swaay; H. Sierdsema (Biodiversity and Conservation, 2023)
While forest productivity and biodiversity are expected to be correlated, prioritizing either forest productivity or biodiversity can result in different management. Spatial quantification of the congruence between areas suitable for either one can inform planning. Here we quantify the relationship between net primary productivity of European forests and biodiversity of mammals, birds, reptiles, amphibians, and butterflies both separately and in combination, and map their spatial congruence. We used richness maps obtained by stacking species distribution models for these animal species, and average net primary production from 2000 to 2012 using moderate resolution imaging spectroradiometer (MODIS) data. We tested how biodiversity and primary productivity are correlated and quantified the spatial congruence of these two sources. We show the areas where high or low productivity co-occur with high or low biodiversity using a quantile-based overlay analysis. Productivity was positively correlated to overall biodiversity and mammal, herptile and butterfly biodiversity, but biodiversity of birds showed a weak negative correlation. There were no significant differences in the strength of relationship across species groups, while herptiles had stronger relationships with productivity compared to other groups. Overlap analysis revealed significant spatial overlap between productivity and biodiversity in all species groups, except for birds. High value areas for both productivity and biodiversity in all species groups, except birds, co-occurred in the Mediterranean and temperate regions. The areas with high biodiversity of birds are mainly found in the boreal areas of Europe, while for all other species groups these areas are mostly located on the Iberian Peninsula and the Balkan ranges. Based on the presented maps, areas where regulating wood production activities to conserve species can be identified. But the maps also help to identify areas where either biodiversity or productivity is high and focusing on just one aspect is more straightforward.

Recruitment, mortality and growth in semi‐arid conifer‐eucalypt forest: Small trees insure against fire and drought - Mathias Neumann; Chris S. Eastaugh; Mark A. Adams (Journal of Biogeography, 2023)
Aim Well‐managed semi‐arid forests help offset global change by storing significant amounts of carbon above‐ and belowground and maintaining hydrological cycles. Larger trees have been the focus of many studies due to their carbon storage and habitat quality, yet recruitment and small trees are important components of ecosystem resilience and recovery. Here, we study the impacts of disturbances (including harvesting) on recruitment, mortality and growth for a mixed conifer‐broadleaf semi‐arid forest type using long‐term data. Location Pilliga Forest in New South Wales, inland eastern Australia. Taxon Callitris‐Eucalyptus forests. Methods We used data from permanent sample plots (PSPs) spanning 55 years, calculated stand structure, gains and losses and determined reasons for tree death (harvesting, fire, wind, drought and other effects). We extracted climate and fire data for the PSP locations using spatial analysis. Results Stocking of studied forests remained stable (modest increase in basal area and stem density), despite harvesting and wildfires over 6 decades. Compared to stands in the 1940s and prior to European settlement, current forests are composed of more trees per unit area, and these trees have smaller diameters. Recruitment and sustained presence of small trees have buffered impacts of recurring drought, fire and harvesting. Fires are a common feature of the studied ecosystems and fire impacts have increased in the past 20 years, especially in unmanaged stands, where fires have reduced tree carbon by >50%. Main conclusions Recruitment and growth of small trees are critical to offset carbon losses due to fire, drought and harvesting. All size classes have important ecological values in semi‐arid forests and must be included in long‐term monitoring programmes. Long‐term data offer unique insights into combined effects of climate change, management and disturbances, especially for fire‐prone ecosystems, where small trees are often susceptible to fire.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Underground salt and potash workers exposed to nitrogen oxides and diesel exhaust: assessment of specific effect biomarkers - Lisa Gamrad-Streubel; Lisa-Marie Haase; Katharina K. Rudolph; Katrin Rühle; Annette M. Bachand; Lori Crawford; Kenneth A. Mundt; Jürgen Bünger; Dirk Pallapies; Dirk Taeger; Swaantje Casjens; Anja Molkenthin; et al. (International Archives of Occupational and Environmental Health, 2022)
Purpose Occupational exposure limits (OEL) for nitrogen oxides (NO, NO 2 ) and diesel exhaust (EC-DPM) were reassessed by the German authorities in 2016/2017. We performed a clinical cross-sectional study among salt and potash underground workers exposed to these substances at relatively high levels to examine possible indicators of acute effects on workers’ health. Methods We measured post- versus pre-shift differences in cardiovascular, inflammatory, immune, and respiratory effect biomarkers and assessed their associations with personal exposures measured during the same shift. We also compared post- versus pre-shift differences in biomarker levels between exposure groups defined based on work site and job type. Results None of the above-ground workers exceeded the OEL for NO 2 and only 5% exceeded the OEL for EC-DPM exposure. Among underground workers, 33% of miners and 7% underground maintenance workers exceeded the OEL for NO 2 ; the OEL for EC-DPM was exceeded by 56% of miners and 17% of maintenance workers. Some effect biomarkers (thrombocytes, neutrophils, MPO, TNF-α, IgE, FeNO) showed statistically significant differences between pre- versus post-shift measurements; however, there were no consistent associations between pre- and post-shift differences and exposure group or personal exposure measurements during the shift. Conclusions We did not find evidence of associations between workplace exposure to NO, NO 2 or EC-DPM and clinically relevant indicators of acute cardiovascular, inflammatory and immune, or respiratory effects among salt and potash underground workers in Germany.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The Journal of Medical Toxicology: Our Once and Future Journal - Howard A. Greller; Peter R. Chai; Natalie R. Neumann; Mark B. Mycyk (Journal of Medical Toxicology, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Amycolatopsis camponoti sp. nov., new tetracenomycin-producing actinomycete isolated from carpenter ant Camponotus vagus - Yuliya V. Zakalyukina; Ilya A. Osterman; Jacqueline Wolf; Meina Neumann-Schaal; Imen Nouioui; Mikhail V. Biryukov (Antonie van Leeuwenhoek, 2022)

Amycolatopsis camponoti sp. nov., new tetracenomycin-producing actinomycete isolated from carpenter ant Camponotus vagus - Yuliya V. Zakalyukina; Ilya A. Osterman; Jacqueline Wolf; Meina Neumann-Schaal; Imen Nouioui; Mikhail V. Biryukov (Antonie van Leeuwenhoek, 2022)
An actinobacterial strain A23 T , isolated from adult ant Camponotus vagus collected in Ryazan region (Russia) and established as tetracenomycin X producer, was subjected to a polyphasic taxonomic study. Morphological characteristics of this strain included well-branched substrate mycelium and aerial hyphae fragmented into rod-shaped elements. Phylogenetic analyses based on 16S rRNA gene and genome sequences showed that strain A23 T was most closely related to Amycolatopsis pretoriensis DSM 44654 T . Average nucleotide identity and digital DNA–DNA hybridization values between the genome sequences of isolate A23 T and its closest relative, Amycolatopsis pretoriensis DSM 44654 T , were 39.5% and 88.6%, which were below the 70% and 95–96% cut-off point recommended for bacterial species demarcation, respectively. The genome size of the isolate A23 T was 10,560,374 bp with a DNA G + C content of 71.2%. The whole-cell hydrolysate contained meso -diaminopimelic acid and arabinose and galactose as main diagnostic sugars as well as ribose and rhamnose. It contained MK-9(H4) as the predominant menaquinone and iso -C 16:0 , iso -C 15:0 , anteiso -C 17:0 and C 16:0 as the major cellular fatty acids. Diphosphatidylglycerol and phosphatidylethanolamine prevailed among phospholipids. Mycolic acids were not detected. Based on the phenotypic, genomic and phylogenetic data, isolate A23 T represents a novel species of the genus Amycolatopsis , for which the name Amycolatopsis camponoti sp. nov. is proposed, and the type strain is A23 T (= DSM 111725 T = VKM 2882 T ).

Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2022)
Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGA t A t genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge value for wheat breeding, the tetraploid GGA t A t genepool is largely neglected. Understanding the population structure, native distribution range, intraspecific variation of the entire tetraploid GGA t A t genepool and its domestication history would further its use for wheat improvement. The paper provides the first comprehensive survey of genomic and cytogenetic diversity sampling the full breadth and depth of the tetraploid GGA t A t genepool. According to the results obtained, the extant GGA t A t genepool consists of three distinct lineages. We provide detailed insights into the cytogenetic composition of GGA t A t wheats, revealed group- and population-specific markers and show that chromosomal rearrangements play an important role in intraspecific diversity of T. araraticum . The origin and domestication history of the GGA t A t lineages is discussed in the context of state-of-the-art archaeobotanical finds. We shed new light on the complex evolutionary history of the GGA t A t wheat genepool and provide the basis for an increased use of the GGA t A t wheat genepool for wheat improvement. The findings have implications for our understanding of the origins of agriculture in southwest Asia.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis - S. Callegaro; H. H. Svensen; E. R. Neumann; A. G. Polozov; D. A. Jerram; F. M. Deegan; S. Planke; O. V. Shiganova; N. A. Ivanova; N. V. Melnikov (Contributions to Mineralogy and Petrology, 2021)
A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin center and periphery, recovered from 15 deep sills intercepted by boreholes. The studied samples are all low-Ti basalt and basaltic andesites, confirming absence of high-Ti and alkaline STLIP magmatism in the Tunguska Basin. The sills derive from picritic parental melts produced by extensive melting of a mantle source with recycled crustal components below a thinned lithosphere (50–60 km), within the spinel stability field. The mantle source was dominantly peridotitic, with enriched pyroxenitic domains formed by recycled lower crust, in agreement with previous models for the main tholeiitic STLIP phase. Limited amounts (up to 5%) of highly radiogenic granitoids or moderately radiogenic metapelites were assimilated in upper crustal magma reservoirs. After emplacement, sills intruded in Cambrian evaporites assimilated marlstones and interacted with the evaporitic host rocks, probably via fluids and brines. This is the first time that such process is described in subvolcanic rocks from all across the volcanic basin. The sills are correlated geochemically with the established chemostratigraphy for the on-craton STLIP lava piles and intrusions (Norilsk region). Sills correlated with the Morongovsky–Mokulaevsky Fm. and the Norilsk-type intrusions are the most voluminous, present all across the central Tunguska Basin, and bear the strongest evidence of interaction with evaporites. Massive discharge of thermogenic volatiles is suggested by explosive pipes and hydrothermal vent structures throughout the Tunguska Basin. We propose that this voluminous pulse of magmatism is a good candidate for the hitherto unidentified early intrusive phase of the STLIP, and may link the deep Tunguska basin sills to the end-Permian environmental crisis.

The place beyond the trees: renewed excavations of the Middle Stone Age deposits at Olieboomspoort in the Waterberg Mountains of the South African Savanna Biome - A. Val; P. de la Peña; M. Duval; S. Bansal; F. Colino; J. Culey; T. Hodgskiss; P. Morrissey; A. Murray; M. Murungi; F.H. Neumann; K. Shadrach; et al. (Archaeological and Anthropological Sciences, 2021)
Olieboomspoort is one of the few rock shelters in the vast interior of southern Africa documenting pulses of occupation from the Acheulean until the end of the Later Stone Age. Revil Mason excavated the site in 1954 and attributed the large Middle Stone Age (MSA) lithic assemblage to his middle phase of the so-called Pietersburg Industry. Recent work at the site has focused on the Holocene layers, but little is known about the earlier phases of shelter use. Here, we provide some background to the shelter, give a history of past research and present initial results following renewed fieldwork at the site. The MSA deposits contain abundant lithic artefacts and ochre, and we present an initial description of these cultural remains. Palynological analysis reveals limited potential for palaeoenvironmental reconstructions, but some faunal remains indicate open grasslands. We dated two equid teeth that provided highly consistent combined U-series-ESR estimates, resulting in a mean age of 150 ± 14 ka (1σ). Even when considering potential sources of uncertainty such as variations in water-intake, these fossils can securely be dated to Marine Isotopic Stage 6. Our reappraisal of site formation processes highlights the fact that the archaeological assemblage is strongly time-averaged. We discuss these different results in the context of a recently rekindled interest in the so-called Pietersburg Industry.

Cost‐effectiveness of longitudinal surveillance for Piscirickettsia salmonis using qPCR in Atlantic salmon farms ( Salmo salar ) in Chile - Marina K. V. C. Delphino; Fernando O. Mardones; Joaquin Neumann Heise; Alicia Gallardo; Daniel Jimenez; Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner (Journal of Fish Diseases, 2021)
Costs of diagnostic testing including sample collection, sampling frequency and sample size are an important consideration in the evaluation of the economic feasibility of alternative surveillance strategies for detection of infectious diseases in aquatic animals. In Chile, Piscirickettsia salmonis is the primary reason for antibiotic treatments in farmed Atlantic salmon. In 2012, a surveillance and control programme for piscirickettsiosis was established with an overall goal of reducing antibiotic use. The present study estimated the cost‐effectiveness of different sampling frequencies and sample sizes to achieve at least 95% confidence of early detection of P. salmonis at the netpen and farm levels using a validated qPCR test. We developed a stochastic model that incorporated variability in test accuracy, within‐pen prevalence and sampling costs. Our findings indicated that the current piscirickettsiosis surveillance programme based on risk‐based sampling of five moribund or dead fish from 2 to 3 netpens is cost‐effective and gives a high probability of detection of P. salmonis in Atlantic salmon farms in Chile at both the netpen and farm levels. Results from this study should incentivize salmon farmers to establish cost‐effective strategies for early detection of P. salmonis infection and the application of this approach to other highly infectious diseases.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Influence of Patient-Specific Characteristics on Transcatheter Heart Valve Neo-Sinus Flow: An In Silico Study - Shelly Singh-Gryzbon; Beatrice Ncho; Vahid Sadri; Sanchita S. Bhat; Sai S. Kollapaneni; Dharani Balakumar; Zhenglun A. Wei; Philipp Ruile; Franz-Joseph Neumann; Philipp Blanke; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2020)

Bayesian estimation of diagnostic sensitivity and specificity of a qPCR and a bacteriological culture method for Piscirickettsia salmonis in farmed Atlantic salmon ( Salmo salar L.) in Chile - Emilie Laurin; Ian A. Gardner; Andrea Peña; Marco Rozas‐Serri; Jorge Gayosa; Joaquin Neumann Heise; Fernando O. Mardones (Journal of Fish Diseases, 2020)
Early detection of piscirickettsiosis is an important purpose of government‐ and industry‐based surveillance for the disease in Atlantic salmon farms in Chile. Real‐time qPCRs are currently used for surveillance because bacterial isolation is inadequately sensitive or rapid enough for routine use. Since no perfect tests exist, we used Bayesian latent class models to estimate diagnostic sensitivity ( DSe ) and specificity ( DSp ) of qPCR and culture using separate two‐test, single‐population models for three farms ( n = 148, 151, 44). Informative priors were used for DSp (culture (beta(999,1); qPCR (beta(98,2)), and flat priors (beta 1,1) for DSe and prevalence. Models were run for liver and kidney tissues combined and separately, based on the presence of selected gross‐pathological signs. Across all models, qPCR DSe was 5‐ to 30‐fold greater than for culture. Combined‐tissue qPCR median DSe was highest in Farm 3 (sampled during P. salmonis outbreak ( DSe = 97.6%)) versus Farm 1 ( DSe = 85.6%) or Farm 2 ( DSe = 83.5%), both sampled before clinical disease. Median DSe of qPCR was similar for liver and kidney, but higher when gross‐pathological signs were evident at necropsy. High DSe and DSp and rapid turnaround‐time indicate that the qPCR is fit for surveillance programmes and diagnosis during an outbreak. Targeted testing of salmon with gross‐pathological signs can enhance DSe .

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Medical Toxicology and COVID-19: Our Role in a Pandemic - Natalie R. Neumann; Peter R. Chai; David M. Wood; Howard A. Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2020)

Habitats and fish communities at mesophotic depths in the Mexican Pacific - Jordan A. Hollarsmith; Georgina Ramírez‐Ortiz; Tallulah Winquist; Manuel Velasco‐Lozano; Katherine DuBois; Héctor Reyes‐Bonilla; Kyle C. Neumann; Edwin D. Grosholz (Journal of Biogeography, 2020)
Aim Mesophotic ecosystems, found at the limit of light penetration in the ocean, are rich in biodiversity and harbour unique ecological communities. However, they remain among the least studied habitat zones on earth due to the high costs and technological limitations. Here, we characterize mesophotic communities in two marine reserves across a range of habitat types, depths and temperatures using submersible technologies, with the goal of understanding the processes that structure these communities across biogeographical regions. Location The Bay of La Paz and the Revillagigedo Archipelago, Mexico. Taxa Fish and algal species. Methods We used a small and inexpensive remotely operated vehicle (ROV) to conduct roving‐swim surveys of major habitat types in depths from 12 to 94 m. With the resulting binary data on the presence of fish species, we used generalized linear mixed models and canonical correspondence analysis to determine whether biogenic habitat, depth and/or temperature best explained species richness and community structure across reef and non‐reef substrate. Results We identified 72 species or genera, including new depth records for nine fish species and a new geographical record for one fish species. Our surveys included large undocumented rhodolith beds (free‐living coralline algae) and mesophotic algal communities, in addition to diverse communities of soft corals and sponges. Fish species richness was positively associated with rocky substrate and warmer water, and reef fish communities differed significantly by depth, temperature and biogenic habitat. Main conclusion Our results highlight the importance of biogenic habitat in structuring communities across gradients of depth and temperature. We also demonstrate the effectiveness of a small and economical ROV for conducting mesophotic surveys in remote regions. Our methods and results provide a framework that can be used to greatly increase the biogeographical and taxonomic scope of mesophotic research, especially for readily identifiable taxa such as fish.

Causes and consequences of Eastern Australia’s 2019–20 season of mega‐fires: A broader perspective - Mark A. Adams; Majid Shadmanroodposhti; Mathias Neumann (Global Change Biology, 2020)

Comparison of three types of laser optical disdrometers under natural rainfall conditions - Lisbeth Lolk Johannsen; Nives Zambon; Peter Strauss; Tomas Dostal; Martin Neumann; David Zumr; Thomas A. Cochrane; Günter Blöschl; Andreas Klik (Hydrological Sciences Journal, 2020)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Crystal structure and configuration revision of 9-hydroxy-7,8-dehydro-sarcotrocheliol and sarcotrocheliol - Abdelaaty Hamed; Marwa Y. Issa; Mohamed A. Ghani; Marcel Frese; Beate Neumann; Hans Georg Stammler; Norbert Sewald; Mohamed Shaaban (Natural Product Research, 2019)

Quantification of PpIX-fluorescence of cerebral metastases: a pilot study - Johannes Knipps; Igor Fischer; Lisa M. Neumann; Marion Rapp; Maxine Dibué-Adjei; Christiane Freiin von Saß; Jan-Malte Placke; Hendrik-Jan Mijderwijk; Hans-Jakob Steiger; Michael Sabel; Jan-Frederick Cornelius; Marcel A. Kamp (Clinical & Experimental Metastasis, 2019)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Limitations of Weight Velocity Analysis by Commercial Computer Program Growth Analyser Viewer Edition - Martin J. C. van Gemert; Cornelis M. A. Bruijninckx; Ton G. van Leeuwen; H. A. Martino Neumann; Pieter J. J. Sauer (Annals of Biomedical Engineering, 2019)

Effects of ketamine on brain function during response inhibition - M. Steffens; C. Neumann; A.-M. Kasparbauer; B. Becker; B. Weber; M. A. Mehta; R. Hurlemann; U. Ettinger (Psychopharmacology, 2018)

Altered monetary loss processing and reinforcement-based learning in individuals with obesity - Jana Kube; David Mathar; Annette Horstmann; Sonja A. Kotz; Arno Villringer; Jane Neumann (Brain Imaging and Behavior, 2018)

Neuromotor and cognitive responses of adults with autism spectrum disorder compared to neurotypical adults - Steven Morrison; Cortney N. Armitano; C. Teal Raffaele; Stephen I. Deutsch; Serina A. Neumann; Hope Caracci; Maria R. Urbano (Experimental Brain Research, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

The bivalve Lembulus bicuspidatus may enhance denitrification in shelf sediment at the Angola–Benguela Frontal Zone - A Neumann; A Flohr (African Journal of Marine Science, 2018)

Fibrobacter communities in the gastrointestinal tracts of diverse hindgut‐fermenting herbivores are distinct from those of the rumen - Anthony P. Neumann; Caroline A. McCormick; Garret Suen (Environmental Microbiology, 2017)
Summary The genus Fibrobacter contains cellulolytic bacteria originally isolated from the rumen. Culture‐independent investigations have since identified Fibrobacter populations in the gastrointestinal tracts of numerous hindgut‐fermenting herbivores, but their physiology is poorly characterized due to few representative axenic cultures. To test the hypothesis that novel Fibrobacter diversity exists in hindgut fermenters, we performed culturing and 16S rRNA gene amplicon sequencing on samples collected from phylogenetically diverse herbivorous hosts. Using a unique approach for recovering axenic Fibrobacter cultures, we isolated 45 novel strains from 11 different hosts. Full‐length 16S rRNA gene sequencing of these isolates identified nine discrete phylotypes (cutoff = 0.03%) among them, including several that were only isolated from hindgut‐fermenting hosts, and four previously unrepresented by axenic cultures. Our phylogenetic analysis indicated that six of the phylotypes are more closely related to previously described subspecies of Fibrobacter succinogenes , while the remaining three were more closely related to F. intestinalis . Culture‐independent bacterial community profiling confirmed that most isolates were representative of numerically dominant phylotypes in their respective samples and strengthened the association of certain phylotypes with either ruminants or hindgut‐fermenters. Despite considerable phylogenetic diversity observed among the Fibrobacter strains isolated here, phenotypic characterization suggests a conserved specialization for growth on cellulose.

Neurobiological mechanisms associated with facial affect recognition deficits after traumatic brain injury - Dawn Neumann; Brenna C. McDonald; John West; Michelle A. Keiski; Yang Wang (Brain Imaging and Behavior, 2016)

Digital and real-habitat modeling of Hipparchia statilinus based on hyper spectral remote sensing data - L. Luft; C. Neumann; S. Itzerott; A. Lausch; D. Doktor; M. Freude; N. Blaum; F. Jeltsch (International Journal of Environmental Science and Technology, 2016)

18,000 years of grassland evolution in the summer rainfall region of South Africa: evidence from Mahwaqa Mountain, KwaZulu-Natal - Frank H. Neumann; Gregory A. Botha; Louis Scott (Vegetation History and Archaeobotany, 2014)

Neuroimaging and facial affect processing: implications for traumatic brain injury - Dawn Neumann; Michelle A. Keiski; Brenna C. McDonald; Yang Wang (Brain Imaging and Behavior, 2014)

Genome wide association mapping to identify aluminium tolerance loci in bread wheat - S. Navakode; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2014)

Human mesenchymal stem cells express a myofibroblastic phenotype in vitro: comparison to human cardiac myofibroblasts - Melanie A. Ngo; Alison Müller; Yun Li; Shannon Neumann; Ganghong Tian; Ian M. C. Dixon; Rakesh C. Arora; Darren H. Freed (Molecular and Cellular Biochemistry, 2014)

A simple model for the estimation of wine characteristics in SW Germany - Paul A. Neumann; Andreas Matzarakis (Theoretical and Applied Climatology, 2014)

Estimation of wine characteristics using a modified Heliothermal Index in Baden-Württemberg, SW Germany - Paul A. Neumann; Andreas Matzarakis (International Journal of Biometeorology, 2014)

Fatty Acid Methyl Esters and Solutol HS 15 Confer Neuroprotection after Focal and Global Cerebral Ischemia - Hung Wen Lin; Isabel Saul; Victoria L. Gresia; Jake T. Neumann; Kunjan R. Dave; Miguel A. Perez-Pinzon (Translational Stroke Research, 2014)

The production and turnover of extramatrical mycelium of ectomycorrhizal fungi in forest soils: role in carbon cycling - A. Ekblad; H. Wallander; D. L. Godbold; C. Cruz; D. Johnson; P. Baldrian; R. G. Björk; D. Epron; B. Kieliszewska-Rokicka; R. Kjøller; H. Kraigher; E. Matzner; et al. (Plant and Soil, 2013)

An association mapping analysis of dormancy and pre-harvest sprouting in wheat - M. A. Rehman Arif; K. Neumann; M. Nagel; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Performance of a novel microarray multiplex PCR for the detection of 23 respiratory pathogens (SYMP-ARI study) - S. Bierbaum; N. Königsfeld; N. Besazza; K. Blessing; G. Rücker; U. Kontny; R. Berner; M. Schumacher; J. Forster; V. Falcone; C. Sand; A. Essig; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Central administration of oxytocin receptor ligands affects cued fear extinction in rats and mice in a timepoint-dependent manner - Iulia Toth; Inga D. Neumann; David A. Slattery (Psychopharmacology, 2012)

Nephron sparing surgery in von Hippel-Lindau associated renal cell carcinoma; clinicopathological long-term follow-up - C. A. Jilg; Hartmut P. H. Neumann; S. Gläsker; O. Schäfer; C. Leiber; P. U. Ardelt; M. Schwardt; W. Schultze-Seemann (Familial Cancer, 2012)

Genetic studies of seed longevity in hexaploid wheat using segregation and association mapping approaches - M. A. Rehman Arif; M. Nagel; K. Neumann; B. Kobiljski; U. Lohwasser; A. Börner (Euphytica, 2012)

Orbit determination of the Lunar Reconnaissance Orbiter - Erwan Mazarico; D. D. Rowlands; G. A. Neumann; D. E. Smith; M. H. Torrence; F. G. Lemoine; M. T. Zuber (Journal of Geodesy, 2012)

Novel Types of Frontotemporal Lobar Degeneration: Beyond Tau and TDP-43 - Ian R. A. Mackenzie; Manuela Neumann; Nigel J. Cairns; David G. Munoz; Adrian M. Isaacs (Journal of Molecular Neuroscience, 2011)

Human antimicrobial proteins in ear wax - M. Schwaab; A. Gurr; A. Neumann; S. Dazert; A. Minovi (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Raman study of apatite amorphised with swift heavy ions under various irradiation conditions - Christian Weikusat; Ulrich A. Glasmacher; Beatrice Schuster; Christina Trautmann; Ronald Miletich; Reinhard Neumann (Physics and Chemistry of Minerals, 2011)

Demersal zooplankton communities from tropical habitats in the southwestern Atlantic - Pedro A. M. C. Melo; Tâmara A. Silva; Sigrid Neumann-Leitão; Ralf Schwamborn; Lucia M. O. Gusmão; Fernando Porto Neto (Marine Biology Research, 2010)

Losartan reduces mortality in a genetic model of heart failure - Sophie Günther; Hideo A. Baba; Steffen Hauptmann; Hans-Jürgen Holzhausen; Claudia Großmann; Karla Punkt; Tina Kusche; Larry R. Jones; Ulrich Gergs; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Heavy-ion irradiation on crystallographically oriented cordierite and the conversion of molecular CO2 to CO: a Raman spectroscopic study - Christian Weikusat; Ronald Miletich; Ulrich A. Glasmacher; Christina Trautmann; Reinhard Neumann (Physics and Chemistry of Minerals, 2010)

Geodetic constraints from multi-beam laser altimeter crossovers - Erwan Mazarico; G. A. Neumann; D. D. Rowlands; D. E. Smith (Journal of Geodesy, 2010)

Ion tracks in apatite at high pressures: the effect of crystallographic track orientation on the elastic properties of fluorapatite under hydrostatic compression - Pascal Schouwink; Ronald Miletich; Angela Ullrich; Ulrich A. Glasmacher; Christina Trautmann; Reinhard Neumann; Barry P. Kohn (Physics and Chemistry of Minerals, 2010)

Classifying polarimetric SAR data by combining expectation methods with spatial context - A. Reigber; M. Jäger; M. Neumann; L. Ferro-Famil (International Journal of Remote Sensing, 2010)

Effects of organic acid treatments on small hive beetles, Aethina tumida, and the associated yeast Kodamaea ohmeri - Marc O. Schäfer; Wolfgang Ritter; Jeff S. Pettis; Peter E. A. Teal; Peter Neumann (Journal of Pest Science, 2009)

Short-sighted evolution of virulence in parasitic honeybee workers (Apis mellifera capensis Esch.) - Robin F. A. Moritz; Christian W. W. Pirk; H. Randall Hepburn; Peter Neumann (The Science of Nature, 2008)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

A computational model to link psychophysics and cortical cell activation patterns in human texture processing - A. Thielscher; H. Neumann (Journal of Computational Neuroscience, 2007)

Mutations in autism susceptibility candidate 2 (AUTS2) in patients with mental retardation - Vera M. Kalscheuer; David FitzPatrick; Niels Tommerup; Merete Bugge; Erik Niebuhr; Luitgard M. Neumann; Andreas Tzschach; Sarah A. Shoichet; Corinna Menzel; Fikret Erdogan; Ger Arkesteijn; Hans-Hilger Ropers; et al. (Human Genetics, 2007)

Regional products for the Baltic Sea using MERIS data - H. Krawczyk; A. Neumann; B. Gerasch; T. Walzel (International Journal of Remote Sensing, 2007)

Remote Non-invasive Stereoscopic Imaging of Blood Vessels: First In-vivo Results of a New Multispectral Contrast Enhancement Technology - F. P. Wieringa; F. Mastik; F. J. ten Cate; H. A. M. Neumann; A. F. W. van der Steen (Annals of Biomedical Engineering, 2006)

Seasonal nestmate recognition in the ant Formica exsecta - Andreas Katzerke; Peter Neumann; Christian W. W. Pirk; Peter Bliss; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2006)

Social parasitism by Cape honeybee workers in colonies of their own subspecies (Apis mellifera capensis Esch.) - S. Härtel; P. Neumann; F. S. Raassen; R. F. A. Moritz; H. R. Hepburn (Insectes Sociaux, 2006)

Ingestion of Large Centric Diatoms, Mangrove Detritus, and Zooplankton by Zoeae of Aratus pisonii (Crustacea: Brachyura: Grapsidae) - R. Schwamborn; W. Ekau; A. P. Silva; S. H. L. Schwamborn; T. A. Silva; S. Neumann-Leitão; U. Saint-Paul (Hydrobiologia, 2006)

Rare royal families in honeybees, Apis melliferas - Robin F. A. Moritz; H. Michael; G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Rare royal families in honeybees, Apis mellifera - Robin F. A. Moritz; H. Michael G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Genetic spatial structure of European common hamsters ( Cricetus cricetus ) — a result of repeated range expansion and demographic bottlenecks - K. NEUMANN; J. R. MICHAUX; S. MAAK; H. A. H. JANSMAN; A. KAYSER; G. MUNDT; R. GATTERMANN (Molecular Ecology, 2005)
The spatial genetic structure of common hamsters ( Cricetus cricetus ) was investigated using three partial mitochondrial (mt) genes and 11 nuclear microsatellite loci. All marker systems revealed significant population differentiation across Europe. Hamsters in central and western Europe belong largely to two allopatric mitochondrial lineages south and northwest of the Carpathian and Sudetes. The southern group, ‘Pannonia’, comprises populations inside the Carpathian basin (Czech Republic, Hungary) while the second group, ‘North’, includes hamsters from Belgium, the Netherlands, France, and Germany. Isolation of the lineages is maintained by a combination of geographical and ecological barriers. Both main phylogeographical groups show signs of further subdivision. North is separated into highly polymorphic central German and less polymorphic western populations, which most likely split during late glacial expansion (15 000–10 000 bp ). Clock estimates based on haplotype distributions predict a divergence of the two major lineages 85 000–147 000 bp . Expansion times fall during the last glaciation (115 000–10 000 bp ) corroborating fossil data, which identify Cricetus cricetus as characteristic of colder climatic phases. Despite the allopatry of mt haplotypes, there is an overlap of nuclear microsatellite alleles between phylogeographical units. Although there are strong evidence that Pannonian hamsters have persisted inside the Carpathian basin over the last 50 000 years, genetic differentiation among European hamsters has mainly been caused by immigration from different eastern refugia. Possible source populations are likely to be found in the Ukrainian and the southern Russian plains — core areas of hamster distribution. From there, hamsters have repeatedly expanded during the Quaternary.

Genetic variance of mating frequency in the honeybee (Apis mellifera L.) - F. B. Kraus; P. Neumann; R. F. A. Moritz (Insectes Sociaux, 2005)

Factors influencing long-term survival in mesothelioma patients?results of the German mesothelioma register - V. Neumann; A. Rtten; M. Scharmach; K.-M. Mller; M. Fischer (International Archives of Occupational and Environmental Health, 2004)

Multiple bottlenecks in threatened western European populations of the common hamster Cricetus cricetus (L.) - K. Neumann; H. Jansman; A. Kayser; S. Maak; R. Gattermann (Conservation Genetics, 2004)

Sperm limitation and the evolution of extreme polyandry in honeybees (Apis mellifera L.) - F. B. Kraus; P. Neumann; J. van Praagh; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 2004)

A technical note for using microsatellite DNA analyses in haploid male DNA pools of social Hymenoptera - R. F. A. Moritz; H. Scharpenberg; H. M. G. Lattorff; P. Neumann (Insectes Sociaux, 2003)

Spatial differences in worker policing facilitate social parasitism of Cape honeybee workers ( Apis mellifera capensis Esch.) in queenright host colonies - P. Neumann; C. W. W. Pirk; H. R. Hepburn; R. F. A. Moritz (Insectes Sociaux, 2003)

The integration of a major hepatitis B virus gene into cell-cycle synchronized carrot cell suspension cultures and its expression in regenerated carrot plants - J. Imani; A. Berting; S. Nitsche; S. Schaefer; W. H. Gerlich; K.-H. Neumann (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Effects of taurolidine and octreotide on port site and liver metastasis after laparoscopy in an animal model of pancreatic cancer - F.A. Wenger; M. Kilian; C. Braumann; A. Neumann; J. Ridders; F.J. Peter; H. Guski; C.A. Jacobi (Clinical & Experimental Metastasis, 2002)

Social encapsulation of beetle parasites by Cape honeybee colonies ( Apis mellifera capensis Esch.) - Neumann P.; Pirk C.; Hepburn H.; Solbrig A.; Ratnieks F.; Elzen P.; Baxter J. (The Science of Nature, 2001)

Somatic embryogenesis and DNA organization of genomes from selected Daucus species - J. Imani; L. Tran Thi; G. Langen; B. Arnholdt-Schmitt; S. Roy; C. Lein; A. Kumar; K.-H. Neumann (Plant Cell Reports, 2001)

Social encapsulation of beetle parasites by Cape honeybee colonies ( Apis mellifera capensis Esch.) - Neumann P.; Pirk C.; Hepburn H.; Solbrig A.; Ratnieks F.; Elzen P.; Baxter J. (The Science of Nature, 2001)

Cereal/legume rotations affect chemical properties and biological activities in two West African soils - S. Alvey; M. Bagayoko; G. Neumann; A. Buerkert (Plant and Soil, 2001)

Storage and formulation of the entomopathogenicnematodes Heterorhabditis indica and H. bacteriophora - O. Strauch; I. Niemann; A. Neumann; A.J. Schmidt; A. Peters; R.-U. Ehlers (BioControl, 2000)

Root-induced increases in soil pH and nutrient availability to field-grown cereals and legumes on acid sandy soils of Sudano-Sahelian West Africa - M. Bagayoko; S. Alvey; G. Neumann; A. Buerkert (Plant and Soil, 2000)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

The influence of cytochrome P450 1A1 and glutathione S-transferase M1 genotypes on biomarker levels in coke-oven workers - G. Brescia; L. Celotti; E. Clonfero; H. G. Neumann; A. Forni; V. Foà; M. Pisoni; G. M. Ferri; G. Assennato (Archives of Toxicology, 1999)

Is bradykinin a mediator of renal neuropeptide Y effects? - A. Bischoff; A. Neumann; A. Dendorfer; M. C. Michel (Pflügers Archiv - European Journal of Physiology, 1999)

Absconding in honeybees ( Apis mellifera ) in relation to queen status and mode of worker reproduction - H. R. Hepburn; S. L. Reece; P. Neumann; R. F. A. Moritz; S. E. Radloff (Insectes Sociaux, 1999)

Is bradykinin a mediator of renal neuropeptide Y effects? - A. Bischoff; A. Neumann; A. Dendorfer; M. C. Michel (Pflügers Archiv - European Journal of Physiology, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Submarine outcrop and acoustic expression of lithified sediment layers in northwest Providence Channel, Bahamas - N. C. Slowey; A. C. Neumann; S. J. Burns (Geo-Marine Letters, 1998)

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Direct actions of serotonin on gonadotropin-II and growth hormone release from goldfish pituitary cells: interactions with gonadotropin-releasing hormone and dopamine and further evaluation of serotonin receptor specificity - A.O.L. Wong; C.K. Murphy; J.P. Chang; C.M. Neumann; A. Lo; R.E. Peter (Fish Physiology and Biochemistry, 1998)

Nestmate recognition and the genetic relatedness of nests in the ant Formica pratensis - M. Beye; P. Neumann; M. Chapuisat; P. Pamilo; R. F. A. Moritz (Behavioral Ecology and Sociobiology, 1998)

Effects of nutrient addition on growth and rhizosphere pH of Leucadendron ‘Safari Sunset’ - A. Silber; R. Ganmore-Neumann; J. Ben-Jaacov (Plant and Soil, 1998)

Mouse chromosome 4 - Beverly A. Mock; Paul E. Neumann; Fred T. Fiedorek (Mammalian Genome, 1997)

Artificial neural network classification of Drosophila courtship song mutants - Eric K. Neumann; David A. Wheeler; Adam S. Bernstein; Jamie W. Burnside; Jeffrey C. Hall (Biological Cybernetics, 1992)

A clonal analysis of Neisseria meningitidis serogroup A - B. A. Crowe; T. Olyhoek; B. Neumann; B. Wall; M. Hassan-King; B. Greenwood; M. Achtman (Antonie van Leeuwenhoek, 1987)

Surface tension of animal cartilage as it relates to friction in joints - Jacques Chappuis; Igor A. Sherman; A. Wilhelm Neumann (Annals of Biomedical Engineering, 1983)

Malate dismutation by Desulfovibrio - J. D. A. Miller; P. M. Neumann; Lynette Elford; D. S. Wakerley (Archives of Microbiology, 1970)